Rancang Bangun Sistem Pendukung Keputusan Pemilihan Supplier Pada Derry Auto Service Dengan Metode AHP - Hasdi, Randy Floranno; Sudarmaningtyas, Pantjawati; Supriyanto, Antok (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
Supplier selection is one important aspect that ensures smooth operations of firms, as well as in Derry Auto Service (DAS). Customers complained that the vehicle has been repaired similar damage after a few months of use because of the quality of the spare part is not replaced either. This happens because DAS just judging by the supplier selection criteria on the price of the cheapest goods. To improve the supplier selection process, DAS requires a decision support system that can process a variety of criteria that is using Analytical Hierarchy Process (AHP). With the supplier selection decision support system is expected to produce recommendations supplier selection results. Results of experiments performed on supplier selection decision support system generates a maximum of 15 criteria and 15 intensity rating. In addition, the application also generates a report on the current best suppliers Kusuma Indah Motor with brand criteria, price, quality, and speed of delivery that produces 0.58  priority value for Shell Helix HX 5 and 1 priority value for Shell Helix HX 7.